2019
DOI: 10.3390/polym11122033
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Application of PVDF and Its Copolymer Films Prepared by Spin-Coating and Langmuir–Blodgett Method

Abstract: Poly(vinylidene fluoride) (PVDF) and its copolymers are key polymers, displaying properties such as flexibility and electroactive responses, including piezoelectricity, pyroelectricity, and ferroelectricity. In the past several years, they have been applied in numerous applications, such as memory, transducers, actuators, and energy harvesting and have shown thriving prospects in the ongoing research and commercialization process. The crystalline polymorphs of PVDF can present nonpolar α, ε phase and polar β, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(73 citation statements)
references
References 228 publications
(359 reference statements)
0
72
0
1
Order By: Relevance
“…Figure 1 b shows a partial magnification of the diffraction peak of the three composites. Strong diffraction peaks at 2 θ = 17.7°, 18.4°, 19.9°, and 26.5° correspond to the α crystallographic reflections: (100), (020), (110), and (021) [ 47 ], and the weak peak at 20.3° is correspond to the (110) and (120) plane of β-phase [ 48 ], indicating the dominance of α-phase in PVDF.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 b shows a partial magnification of the diffraction peak of the three composites. Strong diffraction peaks at 2 θ = 17.7°, 18.4°, 19.9°, and 26.5° correspond to the α crystallographic reflections: (100), (020), (110), and (021) [ 47 ], and the weak peak at 20.3° is correspond to the (110) and (120) plane of β-phase [ 48 ], indicating the dominance of α-phase in PVDF.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…There have been reports of effective coating using PVDF and its copolymers using the spin coating and Langmuir–Blodgett (LB) methods. Yin et al reviewed studies reporting the application of PVDF and its copolymer films using the spin coating and LB methods [ 39 ]. Several studies have reported that PVDF, along with other materials, form a composite or combination of materials that offer the advantages of both materials [ 22 , 23 , 24 , 28 , 29 , 31 , 33 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Biopolymer Coatings For Surface Modificationmentioning
confidence: 99%
“…In addition, as investigated by Mi et al, the dipoles of β crystals relating to the peaks 1401, 1274 and 840 cm −1 are in the orthogonal direction and corresponding relative intensity can be used to determine the lattice orientation 38 . Meanwhile the interaction between C–H … F–C is a dipolar dispersion force, wherein PVDF, a non-conjugated linear fluorinated hydrocarbons and TPS also contain carbon and hydrogen resulting in transient dipole moment lead a separate transient dipole moment in neighboring molecule, initiating a fleeting attraction between the C–H molecules 39 . The remaining characteristic bands were mostly contributed by PVDF which as follows: (1) 3400–3427 cm −1 : stretching vibration mode of the hydrogen-bonded O H groups of starch, (2) 1625–1629 cm −1 : double bond interaction of C to C; (3) 1185–1190 cm −1 the retain stretching vibration of C–F; and the (4) 883–884 cm −1 : confirmed the C=C bonding in bending movement.…”
Section: Resultsmentioning
confidence: 99%